Human Capital Quality and Bank Size: Unpacking Workforce Productivity in Indonesian KBMI 4 Banks - Yazid Abu; Ahmad Syauqi (Economics and Digital Business Review, 2026)
This study aims to analyse the influence of Human Capital Quality and Bank Size on Workforce Productivity in KBMI 4 banks in Indonesia during the 2021–2025 period. Changes in the banking business environment, driven by digital transformation, technological advancements, and increasing operational complexity, have made the quality of human resources and organisational capacity strategic factors in enhancing workforce productivity. This study employed a quantitative approach using the panel data regression method. The sample was selected using a purposive sampling technique based on specific criteria, resulting in four KBMI 4 banks as the research sample with a five-year observation period. Data analysis was conducted using EViews through panel data regression model selection tests, classical assumption tests, the F-test, the t-test, and the coefficient of determination. The results indicate that Human Capital Quality has a positive and significant effect on Workforce Productivity. Furthermore, Bank Size also has a positive and significant effect on Workforce Productivity. Simultaneously, Human Capital Quality and Bank Size have a significant effect on Workforce Productivity. These findings indicate that improving the quality of human resources and strengthening organisational capacity are important factors in enhancing workforce productivity in the large-scale banking industry.